Role of Visual Contrast Sensitivity in Early Detection of Age-Related Macular Degeneration - Ahmed Jamal Khan, Dilshad Alam Khan, Nesr Farooq, Aftab ur Rehman, Piya Muhammad Musammat Rafi, Asif Manzoor, Muhammad Ayub Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Age-related macular degeneration (AMD) often develops gradually, and earlyfunctional changes may go unnoticed during routine eye examinations. Contrast sensitivity decline is believed to occur